Culturally Competent Healthcare and its Impact on Education and Policy Reformation - Marissa Molina; Lisa R. Brown; Elijah Miranda; Erika Montoya; Elisabeth Villarreal; Lisa Caldwell-Serges (Adult Education Research Conference, 2024)
cultural competency, healthcare , diversity, migrants, policy formation, communication, microaggressions, discrimination ,qualitative, quantitative data decision making, program improvement, Higher education, artificial intelligence, incivility, training, community, race, improvement, social justice, educators, inclusivity, administration.
Keywords: diversity; policy; higher education; healthcare